Analisis Tren Kecurangan Laporan Keuangan Perbankan: Pre Dan Post Pandemic Covid Di Indonesia - Kania Nurcholisah; Pupung Purnamasari; Edi Sukarmanto (Jurnal Reviu Akuntansi dan Keuangan, 2023)
Purpose: This study aims to determine the extent of differences in earnings manipulation and the possibility of fraudulent activities in the banking sector in the period before and after the Covid 19 Pandemic in 2016-2021. Methodology/approach: used is quantitative with a verification approach. The data analysis technique used is Descriptive Statistics and Differential Test using Pair Sample T. Test. Financial Report Quality Indicators using the Bernaish Model which consists of 8 indicators, namely the Quality of Days' Sales in Receivable (DSRI), Gross Margin Index (GMI), Asset Quality Index (AQI), Sales Growth Index (SGI), Depreciation Index (DEPI) Sales, General and Administrative Expenses Index (SGAI) Total Accruals to Total Assets (TATA), Leverage Index (LEVI). The population of this study is the banking sector listed on the Indonesia Stock Exchange during the 2017-2021 period, which amounted to 104 data. The Sample Withdrawal Technique used is Purposive Sampling. Findings: The quality of financial statements before and after the Covid Pandemic is not significantly different, although the frequency of financial statement fraud after covid has increased. Practical implications: These finding have implications for companies that indications of financial statement fraud have not changed in the situation before and after the covid pandemic. Originality/value: This study uses the Classical Beneish Model but through the Paires Sample T test method approach in analysing the comparison before and after Pandemic Covid 19.